The history, organization and training of wind bands - Honey, Albert Edward (Rhodes University, Faculty of Humanities, Department of Music, 1973)
From introduction: The decision to use the term "Wind Band" in connection with this work was made after much careful deliberation. The English word "Band" is derived from the French "bande" meaning a group of players. It was first applied in this context in England when the Twenty-four Violins at the Court of Charles II (in emulation of "Le Vingt-quatre Violons du Roi at the Court of Louis XIV of France) were known in England as "The King's Band "Band" is a title generally given at the present time to any of instrumentalists, and indeed, many of the World's most famous conductors have been known to refer to any large symphony orchestra as "The Band" and the dressing-room of every Symphony or Concert orchestra in the British Isles is invariably called "The Band-Room"
Keywords: Band music -- Instruction and study; Band music -- Analysis, appreciation; Bands (Music) -- Instruction and study; Bands (Music)